Fundamentals of applied probability and random processes - Ibe, Oliver C. (Oliver Chukwudi), 1947- (Academic Press, 2014)
This revised edition is designed to provide students with a thorough grounding in probability and stochastic processes, demonstrate their applicability to real-world problems, and introduce the basics of statistics. Its clear writing style and homework problems make it ideal for the classroom or for self-study. The book: demonstrates concepts with more than 100 illustrations, including 2 dozen new drawings; expands readers' understanding of disruptive statistics in a new chapter (chapter 8); provides a new chapter on Introduction to Random Processes with 14 new illustrations and tables explaining key concepts; includes two chapters devoted to the two branches of statistics, namely descriptive statistics (chapter 8) and inferential (or inductive) statistics (chapter 9). --